Идентитетите во Хоматијановиот акт бр. 54 - Nedeski, Viktor (Институт за национална историја, 2020)
The Archbishop of Ohrid Demetrios Chomatenos is one of the most prominent scholars of canonical and secular law of his time. Hе played a decisive role in elevating the position of the Ohrid Archbishopric in the newly emerging geo-political circumstances on the territory of fragmented Byzantine empire in the first few decades of the 13th century. During this period many church and secular dignitaries, as well as citizens of different social strata, were resorting to his authority and to the Ohrid Synod, seeking legal resolution of current disputes of a different nature. The result of this activity of Demetrios Chomatenos is the collection “Ponemata Diaphora” which contains a number of official acts and judgments of the Ohrid throne. On this occasion, the topic of our interest is Act no. 54, which resolves a problem that arose between three identities in a monastery on Mount Athos.